Financial market breakdown due to strategy constraints and information asymmetry - Jie Hu (Federal Reserve Bank of Atlanta, 1995)
This paper demonstrates the relevance of strategy constraints on market makers to the possibility of financial market breakdown when there is information asymmetry between market makers and investors; both the case of competitive market makers and the case of a monopolistic market marker are included. Specifically, the paper discusses three types of strategy constraints on the market makers and their implications for the equilibria. The results call attention to the need for more precise specifications of institutional environments (beyond information asymmetry and the mode of competition/monopoly) when considering the possibility of financial market breakdown.
Keywords: 330; Financial markets; Information theory